Kajian Yuridis Kebijakan Pengelolaan Tambang di Wilayah Kabupaten Situbondo Ditinjau Berdasarkan Undang-Undang Nomor 3 Tahun 2020 tentang Pertambangan Mineral dan Batubara - Naufal, Raid Fikri; Fitri, Icha cahyaning (Indonesian Journal of Law and Justice, 2023)
This research was conducted to find out how mining management policies are reviewed based on Law Number 3 of 2020 concerning mineral and coal mining. In this research, the method used is normative juridical which focuses on the application of rules or norms in positive law to raise, discuss and explain the legal issues raised. Mining is some or all stages of activities in the context of research, management and exploitation of minerals or coal which includes general investigations, exploration, feasibility studies, construction, mining, processing and refining, transportation and sales, as well as post-mining activities. Mining is an activity carried out either simply (manually) or mechanically which includes preparation for scattering, loading and transporting excavated materials. Excavated goods contained in the Indonesian mining jurisdiction are national wealth which is a gift from God in the form of natural deposits.